Impact of Training and Development Programs Employee to Productivity in Industry Hospitality - Ferdiansah, Rudi (Hospitality Management and Operations Journal, 2024)
Industry hospitality face increasingly fierce competition tight and change need fast , demanding customers? improvement quality and productivity employees . Training and development programs employee acknowledged as an important strategy in increase competence , efficiency and satisfaction work , which has an impact directly on performance and power competition company . However , the effectiveness from various training programs This Still need under review more in depth , especially in the sector Hospitality . Research This aiming For evaluate impact of training and development programs to productivity employees in the industry hospitality , with focus on improvement relevant skills? with work , efficiency in serve customers , and satisfaction work . Research This use method quantitative with approach survey . Data collected through questionnaire distributed? to 100 hotel employees who have following training and development programs . Data analysis was carried out use linear regression for determine the impact of training programs to productivity employees . Research results show that the training and development program own influence positive and significant to productivity employees . Employees who participate in this program tend show improvement ability work , efficiency and satisfaction in operate his/her task . Findings This underline importance training sustainable as an improvement strategy quality source Power human in industry hospitality .